Misuse of OTC drugs as a public health problem – a case report of extreme severe hypokalaemia due to OTC drug therapy - Michał Czekalski; Paulina Kaczmarek; Sebastian Słomka (Medycyna Pracy)
Over-the-counter (OTC) drugs taken as intended and according to medical advice are a safe form of disease control. In the public consciousness, they are regarded as harmless agents. Thus, there is a danger of insufficient knowledge about possible side effects, interactions with other drugs or the consequences of taking too high doses. The availability of OTC drugs and social acceptance of their use are sometimes the reason for their recreational use. This article describes the case of a female patient who presented to the emergency department with complaints such as significant weakness, deterioration of exercise tolerance, muscle weakness and dizziness. The subjective examination was deepened with a psychiatric history, which revealed a long-standing intoxication with non-steroidal anti-inflammatory drugs (NSAIDs). In conjunction with the toxicological findings, the reported complaints were considered to be a consequence of NSAIDs abuse and recommendations for therapeutic treatment for addiction were made. The article also discusses recommendations in the field of increasing awareness and prevention of OTC drug abuse and the use of the preventive care system in this area. Med Pr Work Health Saf. 2024;75(6):561–568